Pelatihan Penyusunan Laporan Keuangan Sederhana bagi Pengurus Ta’mir Masjid Baiturrahman Desa Sidosari - Salsabila, Sajaroti Alim; Kahar, Novidhoh; Sarimanah, Dinda Ufiq; Gunawan, Ade; Sholihah, Ria Anisatus; Adinugraha, Hendri Hermawan (Jurnal Pengabdian Pada Masyarakat METHABDI, 2024)
The Financial Management of Baiturrahaman Mosque is currently managed by the Ta'mir Masjid, which then hands over its responsibility to the Mosque Treasurer. Each division can submit to the treasurer directly if there is a need, or each division can make purchases in advance before being claimed to the treasurer. However, this financial management system is considered less effective and not transparent. This training is important considering that so far the Ta'mir management has not recorded and compiled financial reports, even though transparent and accountable financial management is important in managing public funds. This training aims to enable Ta'mir mosques to make simple financial reports for monthly money management. The training uses lectures, tutorials, discussions, and evaluation methods to equip Ta'mir administrators with knowledge and skills regarding basic accounting, recording transactions, and making simple financial reports. The service was held at the Baiturrahman Mosque, Sidosari Village on May 22, 2024, at 15.30 WIB by 2 participants. The results of the training received positive responses from the participants, which showed that the participants understood the training material presented, followed by questions and answers about the problems of mosque financial management and solutions to the problems faced. This activity emphasizes the need for continuous education and assistance to foster good financial governance practices in religious institutions.